2022
DOI: 10.1039/d2tb01048h
|View full text |Cite
|
Sign up to set email alerts
|

A smart hydrogel patch with high transparency, adhesiveness and hemostasis for all-round treatment and glucose monitoring of diabetic foot ulcers

Abstract: The treatment and management of diabetic foot ulcers (DFUs) is a pretty intractable problem for clinical nursing. Urgently, the “Black Box” status of the healing process prevents surgeons from providing...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…The poly(tannic acid)-doped polypyrrole nanofibrils in the poly(acrylamide-acrylate adenine) polymer network-based transparent hydrogel accelerated hemostasis, enhanced cell-to-cell contact, prevented wound infection, facilitated collagen deposition, and stimulated angiogenesis to visibly and efficiently aid the healing of diabetic foot ulcers. 194…”
Section: Transparent Crosslinked Hydrogel Wound Dressingsmentioning
confidence: 99%
“…The poly(tannic acid)-doped polypyrrole nanofibrils in the poly(acrylamide-acrylate adenine) polymer network-based transparent hydrogel accelerated hemostasis, enhanced cell-to-cell contact, prevented wound infection, facilitated collagen deposition, and stimulated angiogenesis to visibly and efficiently aid the healing of diabetic foot ulcers. 194…”
Section: Transparent Crosslinked Hydrogel Wound Dressingsmentioning
confidence: 99%
“…The use of such conductive hydrogels in wound monitoring has therefore been investigated in the literature. 155 For instance, in the study by ref. 155, conductive hydrogel prepared by the assembling of polymer networks, based on in situ formed poly(tannic acid) (PTA)-doped polypyrrole (PPy) nanofibrils in the poly(acrylamide-acrylated adenine) (P(AM-Aa)) polymer.…”
Section: Favorable Properties Of Conductive Hydrogel Dressingsmentioning
confidence: 99%
“…155 For instance, in the study by ref. 155, conductive hydrogel prepared by the assembling of polymer networks, based on in situ formed poly(tannic acid) (PTA)-doped polypyrrole (PPy) nanofibrils in the poly(acrylamide-acrylated adenine) (P(AM-Aa)) polymer. The study showed that in addition to facilitating visual monitoring of wounds, the conductive hydrogel facilitated enhanced “communication” between cells for accelerated hemostasis, while also enabling the monitoring or detection of the glucose levels on wounds.…”
Section: Favorable Properties Of Conductive Hydrogel Dressingsmentioning
confidence: 99%
“…The current invasive wearable blood glucose sensors cause discomfort and raise the risk of infection. As a result, noninvasive wearable point-of-care sensors are being continually developed and improved [ 76 , 77 ], yet there is still significant room for improving their accuracy, repeatability, wearability, and accessibility for end users [ 78 ]. Phenylboronic acid is a well-known saccharide cis -diol binder; however, Anslyn et al proposed an unprecedented mechanism for the interaction of o -aminomethyl phenylboric acid and sugars.…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%